Transnasal transplantation of human induced pluripotent stem cell‐derived microglia to the brain of immunocompetent mice. Issue 10 (26th July 2021) - Parajuli, Bijay; Saito, Hiroki; Shinozaki, Youichi; Shigetomi, Eiji; Miwa, Hiroto; Yoneda, Sosuke; Tanimura, Miki; Omachi, Shigeki; Asaki, Toshiyuki; Takahashi, Koji; Fujita, Masahide; Nakashima, Kinichi; et al.
Abstract: Microglia are the resident immune cells of the brain, and play essential roles in neuronal development, homeostatic function, and neurodegenerative disease. Human microglia are relatively different from mouse microglia. However, most research on human microglia is performed in vitro, which does not accurately represent microglia characteristics under in vivo conditions. To elucidate the in vivo characteristics of human microglia, methods have been developed to generate and transplant induced pluripotent or embryonic stem cell‐derived human microglia into neonatal or adult mouse brains. However, its widespread use remains limited by the technical difficulties of generating human microglia, as well as the need to use immune‐deficient mice and conduct invasive surgeries. To address these issues, we developed a simplified method to generate induced pluripotent stem cell‐derived human microglia and transplant them into the brain via a transnasal route in immunocompetent mice, in combination with a colony stimulating factor 1 receptor antagonist. We found that human microglia were able to migrate through the cribriform plate to different regions of the brain, proliferate, and become the dominant microglia in a region‐specific manner by occupying the vacant niche when exogenous human cytokine is administered, for at least 60 days. MAIN POINTS: A novel and easy method for replacement of mice microglia with iPSMG was developed by combining CSF1R antagonist with transnasal iPSMG transplantation. This method is noninvasive, efficient, and does not require immunosuppression of recipients.